PENGARUH MOTIVASI KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN DI MODERASI KOMPENSASI - Djaya, Subhan (Buletin Studi Ekonomi; VOL.26.NO.1.FEBRUARI 2021DO - 10.24843/BSE.2021.v26.i01.p06, 2021)
Compensation is used as a moderating variable in explaining motivation and competence towards employee performance. This research is meant in an explanatory research study which is used to prove the response of 97 employees to the variables studied. SEM analysis of WarpPLS 7.0 is used to answer the hypothesis in this study, the results show that low motivation is not able to improve employee performance and high competence has not been able to improve employee performance, on the other hand it explains that with good compensation support, it will be able to contribute which is real in increasing the influence of motivation and competence on performance to be significant, this is because the existence of a fair compensation system and in accordance with the workload of employees, will motivate them to work and maximize the competence of employees in completing their duties